Chapter Gli strumenti - Zingaro, Mariella (Studi e saggi, 2020)
In this contribution, the financial and planning instruments that can promote the development of a Community-based cooperative are analysed. In particular, EU cohesion policy and rural development programs are considered. A focus is then made on the so-called InvestEU Fund, and another in-depth look is given to Smart Villages, which are defined as communities in inner areas using innovative solutions to improve their resilience, building on local strengths and opportunities: a very well suited definition to the potential role of Community-based cooperatives.